The Effect Of Social Media Marketing On Customer Purchase Intention : The Case Of Vidio As Video Streaming Platform - Insan Ariandanu Sufajar; Nurdin Sobari (Eduvest - Journal of Universal Studies, 2024)
Active social media users in Indonesia have increased in 2022. Consequently, several companies, including Vidio, are leveraging to use social media as a tool for their marketing activities, specifically to influence customers' intention to buy their products. This study aims to analyze the influence of social media marketing on customer’s purchase intentions through Customer Equity Drivers and Customer Inspiration as a mediating variable on the Vidio Brand as a Video Streaming Platform. The data was collected from 200 respondents who had not previously purchased a product from Vidio. The data was analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The Findings show that social media marketing activities have significantly influenced all drivers of customer equity and customer inspiration. But the two drivers of customer equity, namely value equity and brand equity, do not significantly influence customer purchase intentions; customer inspiration variables significantly influence purchase intentions; and social media marketing activities do not have a significant effect on direct purchase intentions.